PERSEPSI PELAKU INDUSTRI KAYU TERHADAP IMPLEMENTASI SISTEM VERIFIKASI LEGALITAS KAYU - Pratama, Sutriyadi; Susdiyanti, Tun; Hasibuan, Ratna Sari (Universitas Nusa Bangsa, 2018)
The issue of deforestation and forest degradation in Indonesia led to allegations of illegal logging practices against Indonesian timber products on the world market , so the stakeholder initiative to boost market confidence returning to the Indonesian wood products . Awareness of domestic industry actors against SVLK is still minimal.Â Perception of actors who own S-LK is to gain the trust of customers, improve customer loyalty and ideals, have the legal recognition of the government's efforts, increase the value of its product, reducing the unofficial levies. While the perception of actors who do not have S-LK is their expensive cost factor, ordinances S-LK -making procedures are complicated, and does not know the procedure of making Sâ€“LK